1989
DOI: 10.1021/np50066a009
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Novel Tyrosine Kinase Inhibitor, Lavendustin A, from Streptomyces griseolavendus

Abstract: A potent tyrosine kinase inhibitor, lavendustin A [1], has been isolated from a butyl acetate extract of Streptomyces griseolavendus culture filtrate. It inhibits epidermal growth factor receptor-associated tyrosine kinase with an IC50 of 4.4 ng/ml, which is about 50 times more inhibitory than erbstatin. It does not inhibit protein kinase A or C. Its structure, determined by spectral data and total synthesis, is novel, having a tertiary amine in the center with substituted benzyl and phenyl groups. Lavendustin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
176
1
3

Year Published

1994
1994
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(184 citation statements)
references
References 3 publications
4
176
1
3
Order By: Relevance
“…Here we show for the first time that the angiogenic activity of VEGF in vivo can be prevented by lavendustin A. Lavendustin A is a potent and selective PTK inhibitor in vitro, with an IC50 of 11 nM. In contrast, the IC50 of its negative control, lavendustin B, is 1.3 jiM (Onoda et al, 1989). Thus, the ability of lavendustin A and B to suppress VEGF-induced angiogenesis is entirely consistent with their relative potency as PTK blockers.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Here we show for the first time that the angiogenic activity of VEGF in vivo can be prevented by lavendustin A. Lavendustin A is a potent and selective PTK inhibitor in vitro, with an IC50 of 11 nM. In contrast, the IC50 of its negative control, lavendustin B, is 1.3 jiM (Onoda et al, 1989). Thus, the ability of lavendustin A and B to suppress VEGF-induced angiogenesis is entirely consistent with their relative potency as PTK blockers.…”
Section: Discussionsupporting
confidence: 71%
“…Since the mitogenic and angiogenic activities of VEGF are thought to be mediated by distinct membranespanning tyrosine kinase receptors, we predicted that specific inhibitors of protein tyrosine kinase (PTK) should block the biological functions of VEGF in vivo. To test this hypothesis, we used a highly potent and specific PTK inhibitor lavendustin A (Onoda et al, 1989;Odell et al, 1991) and showed that it is an effective inhibitor of the angiogenic activity of VEGF. Suramin is an effective analogue of heparin/heparan sulphate which inhibits the activities of several heparin-binding growth factors such as fibroblast growth factors (FGFs) and platelet-derived growth factor . Although suramin blocks the growth-stimulating activity of VEGF in vitro (Olander et al, 1991), its action against VEGF in vivo is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic application of lavendustin A has been shown to inhibit the EGF-receptor-associated tyrosine kinase at very low concentration under in vitro condition (IC 50 of ca. 12 nM; Onoda et al, 1989). However, it has been also found that lavendustin A does not inhibit the tyrosine kinase in situ (Onoda et al, 1990).…”
Section: Discussionmentioning
confidence: 98%
“…Also half of all proto-oncogenes discovered so far code for proteins with PTK activity; [19] thus, there is an intensive search underway for selective inhibitors of PTKs. [20] [21] lavendustin A 2, [22] and the tyrphostines 3, [20a,b,e] (Fig. 1).…”
Section: Inhibition Of Protein Tyrosine Kinases (Ptks)mentioning
confidence: 99%